Research trends and prospects on brain metastasis from breast cancer: A bibliometric analysis - Wu, Si-qi; Liu, Yan; Zhou, Jie; You, Yan-ting; Zhou, Xing-hong; Chen, Li-qian; Kwan, Hiu Yee; Zhao, Xiao-shan; Wu, Yi-fen; Liu, Yan-yan (Frontiers in Oncology, 2023)
Introduction: Brain metastasis has been the terminal event of breast cancer with poor prognoses. Therefore, this article aimed at summarizing the development, hotspots, and trends of brain metastasis from breast cancer based on bibliometric analysis. Method: Publications on brain metastasis from breast cancer were retrieved from the Web of Science Core Collection. CiteSpace, VOSviewer and other online bibliometric analysis platforms were used to analyze and visualize the result. Result: In totality, 693 researchers from 3623 institutions accross 74 counties and regions published 2790 papers in 607 journals. There was a noticeable increase in publications in 2006. The United States was the dominant country with most publications followed by China. University Texas MD Anderson Cancer Center was the most productive institution while Dana Farber Cancer Institution was the most cited. Journal of Neuro-Oncology published the most papers while Journal of Clinical Oncology ranked first based on co-cited analysis. Nancy U. Lin was the most productive and cited author with high influence. There was a focus on basic research, clinical trials, local therapy, treatment optimization, and epidemiological studies regarding brain metastases from breast cancer. References focused on pathogenesis, prevention, treatment and prognosis were cited most frequently, among which clinical trial of novel treatment attracted most attention from researchers. Reference citation burst detection suggested that new therapies such as novel TKI and ADC may lead the research trends in the future Conclusion: High-income countries contributed more to the field of brain metastasis from breast cancer while developing countries like China developed more quickly. What’s more, success of novel therapies in recent years may lead to the new era of treatment of brain metastasis from breast cancer in the future.